Rolling out climate smart Cocoa through public-private partnership in Ghana: A Framework highlighting the step-by-step procedure towards climate smart cocoa finance in Ghana - Dalaa, Mustapha Alasan; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The cocoa industry has been the mainstay of the Ghanaian economy over the years through the provision of revenues from foreign exchange earnings and the generation of employment for farmers who are mainly small holders. Climate change is a phenomenon that has been taking place throughout history but over the last century it has accelerated and scientists believe it is increasingly due to human activities (Cook et al, 2016). The climate in Ghana has likewise been affected and it is having an impact on agricultural production and therefore cocoa. Thus, cocoa farming areas have been delineated into three climatic impact zones – Cope, Adjust and Transform. The Consultative Group for International Agricultural Research (CGIAR) through the International Institute of Tropical Agriculture (IITA) in Ghana together with the Rainforest Alliance has recently documented and aligned Climate Smart Cocoa practices across the three impact zones to help farmers mitigate the effects of climate change. This document is a step-by-step process to facilitate the partnership among public and private sector financing of Climate smart cocoa (CSC).